Pengaruh Promosi dan Iklan di Media Sosial Terhadap Volume Penjualan Pada UD. TANDA SETIA - Henni Wika Harefa; Maria Magdalena Bate'e; Martha Surya Dinata Mendrofa; Serniati Zebua (LPPM Universitas HKBP Nommensen, 2025)
This research is a quantitative study with an associative nature. The purpose of this study is to determine the impact of promotions and advertisements on social media on sales volume at UD. Tanda Setia located in Gunungsitoli City. This research uses primary data collected through questionnaires and interviews. In this study, the researcher employs quantitative analysis, multiple linear regression analysis, and the coefficient of determination analysis with the help of SPSS 30. The population in this study consists of all employees and customers of UD. Tanda Setia who have ever made a purchase at UD. Tanda Setia. The results of the research, based on the t-test and F-test, show that both promotions and advertisements have a positive and significant impact on sales volume. In the coefficient of determination test, the results indicate that 92.7% of the variance in sales volume can be explained by promotions and advertisements, while the remaining 7.3% can be explained by other variables not included in this study.